Performance measurement implementation on the smart fisheries village website using pagespeed insight - Panduwika, Panduwika; Solehatin, Solehatin (Journal of Soft Computing Exploration, 2024)
Websites have become the primary way organizations and individuals to communicate, provide information, and offer daily services. The purpose of creating the Smart Fisheries Village (SFV) website was to enhance the performance and quality of the user experience by measuring and optimizing image sizes using Google's tools, specifically Google PageSpeed Insight. We monitored and analyzed the implementation performance to ensure faster loading times without compromising visual quality. The implementation results showed significant improvements in the SFV loading speed, leading to a more satisfactory user experience. To identify images that slow website loading, we used data from PageSpeed Insight. After implementing improvements, we distributed a questionnaire to users to evaluate the development results. The results of the questionnaire revealed a significant increase in user satisfaction with the loading speed and quality of the user experience of the Bangsring Smart Fisheries Village (SFV) website. These findings provide valuable information for the continued development and optimization of website performance in the future. Therefore, this research makes a valuable contribution to improving the performance and user experience of the Bangsring Smart Fisheries Village (SFV) website.